New Afrotropical and Oriental species of Micrepimera Matile (Diptera: Keroplatidae) - Ševčík, Jan; Papp, László (Zootaxa, 2011)
Two new species of Robsonomyiini (Diptera: Keroplatidae: Macrocerinae), Micrepimera berentiana sp. n. and M. pandastica sp. n., are described from southern Madagascar and northern Vietnam, respectively. This is the first record of this tribe in the Afrotropical region and from mainland Asia. Both the new species differ from M. punctipennis Matile (described from Christmas Island in the Indian Ocean) mainly in wing coloration, structure of antennae, and details of the male terminalia.